Effective size closely approximates the census size in the heavily exploited western Atlantic population of the sandbar shark, Carcharhinus plumbeus - Portnoy, David S; McDowell, Jan R; McCandless, Camilla T; Musick, John A; Graves, John E (Conservation genetics, 2009)
The sandbar shark, Carcharhinus plumbeus, is a long-lived species with low lifetime fecundity that is heavily fished in the western North Atlantic. Inshore nursery grounds increase survivorship of sandbar shark pups and the principal nurseries are in the mid-Atlantic region. We calculated effective number of breeders (Nb) and effective population size (Ne) for adults utilizing the nursery grounds of the Delaware Bay and the Eastern Shore of Virginia by genotyping 902 animals across five cohorts at eight microsatellite loci. Estimates of Nb and Ne were compared to estimates of census size (Nc) of cohorts obtained from Delaware Bay. The estimated Ne/Nc and Nb/Nc ratios were 0.45 or higher whether the Delaware Bay cohorts were considered as distinct year classes or combined. This is in contrast to estimated Ne/Nc ratios in other exploited marine fishes, which are several orders of magnitude smaller. Instead, the Ne/Nc ratio of sandbar sharks is similar to that found in marine and terrestrial mammals.